Modification of exogenous CO2 on the pathway of microbial degradation coal to CH4: From the view of stable isotope. (1st May 2023) - Wang, Qiong; Xu, Hao; Tang, Dazhen; Ren, Pengfei
Highlights: Stable isotopes were utilized to qualitatively and quantitatively characterize thermogenic and biogenic gas in the Miquan and Fukang areas. Differences in the pathways of microbial degradation of coal to CH4 in the Miquan and Fukang areas were identified. He and Ne isotopes were used to determine the source and timing of excess CO2 in the Miquan area. Modification of the microbial degradation pathway of coal to CH4 by exogenous CO2 was proposed for the first time. Abstract: The sources of CO2 in coalbed gas (CBG), and their geological significance have been widely discussed. However, the influence of exogenous CO2 on the pathway of microbial degradation of coal to CH4 has not been identified and carefully discussed. To investigate the modification of exogenous CO2 on microbial degradation coal to CH4 pathways, 22 CBG and coproduced water samples from the Miquan and Fukang areas of the southern Junggar Basin were sampled in this study and tested for stable isotopes. The results show that there are significant differences in CBG composition and genesis between Miquan and Fukang areas. The CBG in the Fukang area is mainly CH4, and the thermogenic gas and biogenic gas account for 32.8% − 34.1% and 65.9% − 67.2%, respectively. Almost all the biogenic gas is produced by the CO2 reduction pathway. Unlike the Fukang area, the CBG in the Miquan area has a high CO2 concentration (2.0% to 36.9%). He and Ne isotopes indicate that CO2 in the Miquan area are mainly of crustal origin and have undergone at least 72.5% loss and dilution. Almost all CBG in Miquan area is of biological origin (92.3% to 92.9%). However, the production pathway of biogas is very different from that of Fukang. The CO2 reduction pathway and acetic acid/methyl fermentation pathway account for 65.2% − 79.3% and 20.7% − 34.8%, respectively. The thermogenic gas and biogenic gas in the two areas are from Early Cretaceous and Pleistocene, respectively. The only difference is that CBG in Miquan area was intruded by crustal-derived CO2 during middle to late Miocene. Crust-derived CO2 was utilized by microorganisms to produce enough CH3 COOH, which provided sufficient substrate for microorganisms to produce CH4 using CH3 COOH. Disturbance by exogenous CO2 explains differences in microbial methanogenic pathways in two areas. This study not only clarifies the fate of CO2 in the Miquan area, but also raises the principle of modification of microbial methanogenic pathways by exogenous CO2 .